The international system : theoretical essays - Knorr, Klaus, 1911-1990; Verba, Sidney (Princeton legacy library., 2019)
A sample of recent thinking in international relations theory, World Politics, October 1961, is offered also in a special hard-cover edition. Contributors: M.A. Kaplan, A.L. Burns, T.C. Schelling, R.E. Quandt, J.D. Singer, S. Verba, G. Modelski, F.W. Riggs, C. McClelland, S. Hoffmann. Originally published in 1961. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.